(untitled) (Global Scientific Review, 2022)
Crowdstorming, a collaborative methodology, intents to inquire and determine if this crowd-based process will serve as a contributing factor in the brand image development.The study utilized qualitative method design to capture the qualitative data and inputs from the entrepreneurs as participants. It utilized fifteen entrepreneurs as participants of the study based on the criteria the researchers have considered such as willingness to participate and the experiences that give their products a new brand image. Findings of the study showed that crowdstorming was beneficial in the brand image development of the entrepreneurs. Specifically, customers and suppliers were found to be partners of the entrepreneurs in generating diverse solutions to the business problems faster and in a more transparent way. As part of crowdstorming, they were considered to be in better position to propose innovative ideas related to value proposition and value delivery of the products. Hence, crowdstorming as an innovation tool may lead the entrepreneurs in achieving favorable brand image and can be utilized by all businesses, no matter what the size and type of business is. It should not only be part of brand image development process but also be part of the strategic management process of the business.